2005
DOI: 10.1016/j.cub.2005.09.039
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs-Dependent Signaling of DNA Damage in Dictyostelium discoideum

Abstract: DNA double-strand breaks (DSBs) can be repaired by either homologous recombination (HR) or nonhomologous end-joining (NHEJ). In vertebrates, the first step in NHEJ is recruitment of the DNA-dependent protein kinase (DNA-PK) to DNA termini. DNA-PK consists of a catalytic subunit (DNA-PKcs) that is recruited to DNA ends by the Ku70/Ku80 heterodimer. Although Ku has been identified in a wide variety of organisms, to date DNA-PKcs has only been identified experimentally in vertebrates. Here, we report the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 32 publications
1
76
1
Order By: Relevance
“…Initially, Block et al and Hudson et al identified putative orthologues of Ku70 and Ku80 in the Dictyostelium genome. 49,50 Notably, Dictyostelium Ku80 contains a conserved C-terminal domain that is apparent only in organisms that possess DNA-PKcs and that is required to recruit this protein to sites of DNA damage. 51 These observations lead to speculation that Dictyostelium might contain an orthologue of DNA-PKcs and consistent with this hypothesis, an open reading frame that bares homology to this protein has been identified in the genome of this organism.…”
Section: Conservation Of Non-homologous End-joining In Dictyosteliummentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, Block et al and Hudson et al identified putative orthologues of Ku70 and Ku80 in the Dictyostelium genome. 49,50 Notably, Dictyostelium Ku80 contains a conserved C-terminal domain that is apparent only in organisms that possess DNA-PKcs and that is required to recruit this protein to sites of DNA damage. 51 These observations lead to speculation that Dictyostelium might contain an orthologue of DNA-PKcs and consistent with this hypothesis, an open reading frame that bares homology to this protein has been identified in the genome of this organism.…”
Section: Conservation Of Non-homologous End-joining In Dictyosteliummentioning
confidence: 99%
“…51 These observations lead to speculation that Dictyostelium might contain an orthologue of DNA-PKcs and consistent with this hypothesis, an open reading frame that bares homology to this protein has been identified in the genome of this organism. 49,50 Putative orthologues of the core NHEJ machinery, including DNA Ligase IV, XRCC4 and Artemis are also present in the Dictyostelium genome. 49 The identification of Figure 2.…”
Section: Conservation Of Non-homologous End-joining In Dictyosteliummentioning
confidence: 99%
See 3 more Smart Citations